(untitled) (Research, Society and Development, 2024)
The Federal Institutes of Education, Science and Technology offer integrated secondary education, which is characterised by its commitment to training people for the world of work and life in society. However, bullying, a form of violence that occurs in many school institutions, can be a challenge, even in an education with an omnilateral training perspective. In view of this, this study aimed to investigate how school institutions can contribute to tackling the phenomenon of bullying, with the aim of achieving an increasingly favourable and healthy environment for the broad development of students. The methodological approach of this study was qualitative, using a literature review and a case study as research methods. Data was collected using questionnaires and semi-structured interviews, and the data was analysed using the content analysis theory. Through this research, it was possible to deduce that students expect that education professionals can contribute to combating school bullying through effective actions to this end. It is therefore necessary for each school institution to implement prevention and intervention actions to tackle this phenomenon, seeking the most appropriate forms according to the local reality.